Evaluation and Monitoring of Islamic Education Learning Management in Efforts to Improve Education Quality - Muh Ibnu Sholeh (Al-Qalam Institute, 2023)
This research aims to provide a deeper understanding of the importance of evaluation and monitoring in an effort to improve the quality of Islamic education and to realize it practically in improving the quality of Islamic education through evaluation and monitoring. This study uses library research methods (library research). The data obtained from the literature study were analyzed using an interactive qualitative model. This data analysis model consists of data collection, data reduction, data presentation, and drawing conclusions. The results of this study indicate that the importance of evaluation and monitoring in the management of Islamic education learning includes improving the quality of education, optimizing the learning process, measuring the success of curriculum implementation, helping strengths and weaknesses, measuring student progress, increasing accountability and facilitating the right decision making. Several practical realizations in improving the quality of Islamic education through evaluation and monitoring include proper lesson planning, feedback to teachers, development of teacher professionalism, coaching and mentoring of teachers, curriculum improvement, involvement of students and parents and use of technology in evaluation and monitoring.